Woven endobridge embolization versus microsurgical clipping for unruptured wide-neck cerebral aneurysms on middle cerebral artery bifurcation - Jun Hyeong Park; Hyun Jin Han; Jung-Jae Kim; Yong Bae Kim; Keun Young Park (BMC Neurology)
Abstract Woven EndoBridge (WEB) is an endovascular treatment for wide-neck bifurcation aneurysms (WNBAs). This study aimed to clarify the efficacy and safety of the WEB comparing to clipping for treating the middle cerebral artery (MCA) WNBAs. For the matched analysis, we designed a retrospective, tertiary, single-center study including 288 MCA WNBAs treated with WEB (n = 37) or clipping (n = 251). Inverse probability of treatment weighting (IPTW) for the main analysis and 1:2 propensity score matching for the sensitivity analysis were used to adjust for aneurysm geometric parameters. Morbidity, major complications, and aneurysm occlusion grade were assessed at 1 year. In the IPTW analysis, no significant difference was observed in morbidity (2.1% vs. 1.6%, odds ratio [OR]: 1.34, p = 0.776) and major complications (3.3% vs. 3.1%, OR: 1.08, p = 0.926). Adequate aneurysm occlusion was achieved in 76.1% of the WEB group and 97.4% of the clipping group (OR: 0.09, p < 0.001). In line with the main analysis, the 1:2 propensity score matching analysis revealed no significant difference in the morbidity (OR: 2.00, 95% CI: 0.13–31.98, p = 0.624). This study supports that microsurgical clipping still requires to play a vital role, but WEB could be an alternative option for WNBAs in the MCA.